A NEURAL NETWORK MODEL FOR AUTOMATED LOGISTICS PROVIDER SELECTION - Maratovna, Mirzanova Nozima (Journal of Artificial Intelligence and Digital Economy, 2024)
In the article, using artificial intelligence technologies in the digital economy, the problems of organization of logistics flows were identified and scientific proposals aimed at solving them were developed